A Comparative Study of Rural Schools in Texas, New Mexico, and Arizona - Barker, Bruce O.; Muse, Ivan D. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
A study of K-12 rural school districts enrolling 900 students or fewer in Texas, New Mexico, and Arizona used data gathered during the 1981-82 academic year. These data were compared with those from a nationwide survey using the same questionnaire. Qualifying districts were identified: 626 in Texas (56.9% of all Texas public school districts, enrolling 223,704 students), 43 in New Mexico (48.9%, enrolling 16,648 students), and 21 in Arizona (9.8%, enrolling 11,018 students). Questionnaires relating to rural districts, school superintendents, teachers, student performance, and school programs were mailed to superintendents of 816 randomly selected rural districts nationwide and to 124 Texas districts, 23 New Mexico districts, and 5 Arizona districts. Return rates were 78.7% (642 questionnaires) from the nationwide survey, 67.7% (84) from Texas, 73.9% (17) from New Mexico, and 80% (4) from Arizona. Findings indicated that status and conditions of rural American schools differ between geographical regions and within the same region, and that in the Southwest, particularly Texas and New Mexico, rural school districts comprise a sizeable portion of public school districts in the region. Comparisons of the statistical data from the Southwest states with those from the national survey are presented in a 3-page table. (MH)
ERIC Note: Paper presented at the Annual Southwestern Conference for Rural Education (3rd, Las Cruces, NM, November 11-12, 1983).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Comparative Analysis; Elementary Secondary Education; National Surveys; Regional Characteristics; Resource Staff; Rural Education; Rural Schools; School Activities; School Districts; Small Schools; State Surveys; Student Teacher Ratio; Superintendents; Teacher Distribution; Teacher Salaries; Teachers; United States (Southwest); Arizona -- New Mexico -- Texas; Reports, Research; Speeches/Meeting Papers